Understanding Stuart Hall - Davis, Helen (SAGE Publications, 2004)
Tracing the development of one of the most influential and respected figures within cultural studies, Helen Davis focuses on Stuart Hall's writings over a period of nearly fifty years, offering students and academics a cogent and exploratory route through complex and overlapping areas of analysis.